Rules don't apply [videorecording (DVD)] - Beatty, Warren, 1937-; Beatty, Warren, 1937-; Baldwin, Alec, 1958-; Bening, Annette; Bennett, Haley, 1988-; Bergen, Candice, 1946-; Broderick, Matthew, 1962-; Coleman, Dabney, 1932- (20th Century Fox Home Entertainment, 2017)
Hollywood, 1958. Small town beauty queen and devout Baptist virgin Marla Mabrey, under contract to the infamous Howard Hughes, arrives in Los Angeles. At the airport, she meets her driver Frank Forbes, who is engaged to be married to his seventh grade sweetheart and is a deeply religious Methodist. Their instant attraction puts their religious convictions to the test, and also defies Hughes' number one rule: No employee is allowed to have any relationship whatsoever with a contract actress.